Toward Digital Islamic Finance Technology by Blockchain - Sandiko Yudho Anggoro; Khoirul Umam (Universitas Darussalam Gontor, 2023)
Fintech has made new achievements with IoT by developing web 3.0. This was clarified by the rise of blockchain and bitcoin in 2009, as well as the emergence of digital art assets and the procedures for transacting. However, blockchain technology's advantages that bring are weaknesses at the same time, because it creates a quandary in the established digital financial order. In this case, digital Islamic finance which is still a start-up when compared to the capitalist makes it a dilemma, how to respond to the transformations and developments of this digital financial system. For this reason, this research tries to examine and offer a blockchain-based digital economic system. This study uses an in-depth interview method with several experts and uses a bibliometric approach to achieve it. The findings from this study performance the accountability of coins as currency has a balance of positive legal ethics transparency and the probability of prohibition in digital financial transactional. Furthermore, based on accountability and transparency the blockchain system can be a solution to some weaknesses in digital finance. The main idea of blockchain technology is a ledger that functions to record, confirm, and transfer data flawlessly.